EFEKTIVITAS METODE PRAKTIKUM TERHADAP HASIL BELAJAR PSIKOMOTORIK FISIKA SISWA SMA NEGERI 3 RAMBAH HILIR - Hatika, Rindi Genesa; Siregar, Pariang Sonang (Edu Research, 2016)
This research aims to determine the psychomotor abilities of student in learning physics based on practical method in SMA Negeri 3 Rambah Hilir. The design used in this research is the design of One-Shot Case Study. While the sample of thisresearch is the class XA SMA Negeri 3 Rambah Hilir by the number of students is 27 students.Determination of the sample was conducted using purposive sampling technique. The instrument used in this study is in the form of a guide sheet practicum and performance assessment. Data analysis performed in this study is effectiveness ratio to determine how big the percentage of target achieved on the targets set in thepractical implementation. The results of the analysis showed that the average classical completeness is equivalent to 85% with complete categories and the average ratio of effectiveness in classical amounted to 93.1% with the effective category. Thismeans that the use of practical method is effective in the psychomotor abilities of student in learning physics at SMA Negeri 3 Rambah Hilir.